Experimental and CFD evaluation of ozone efficacy against coronavirus and enteric virus contamination on public transport surfaces. Issue 5 (October 2021) - Falcó, Irene; Randazzo, Walter; Sánchez, Gloria; Vilarroig, Jose; Climent, Javier; Chiva, Sergio; Chica, A.; Navarro-Laboulais, J.
Abstract: The limited information about the routes of the transmission of SARS-CoV-2 within the ongoing pandemic scenario mobilized the administration, industry and academy to develop sanitation and disinfection systems for public and private spaces. Ozone has been proposed as an effective disinfection method against enveloped and non-enveloped viruses, including viruses with similar morphology to SARS-CoV-2. Due to this efficacy, numerous gaseous and aqueous phase ozone applications have emerged potentially to inhibit virus persistence in aerosols, surfaces, and water. In this work, a numerical model, a RANS CFD model for ozone dispersion inside tram and underground coach has been developed including the chemical self-decomposition and surface reactions of the ozone. The CFD model has been developed for a real tram coach of 28.6 × 2.4 × 2.2 m (L × W × H) using 1.76 million nodes and the Menter's shear stress transport turbulence model. The model predicts the O3 concentration needed to meet disinfection criteria and the fluid dynamics inside the public transport coach. The effectiveness of the system has been validated with laboratory and field tests in real full-scale coach using porcine epidemic diarrhea virus (PEDV) and murine norovirus (MNV-1) as SARS-CoV-2 and human norovirus surrogates, respectively. Lab-scale experiments on plastic surfaces demonstrated O3 disinfection (100 ppm, 95% RH, 25 min) inactivate > 99.8% MNV-1 and PEDV. Additionally, field tests in real full-scale coach demostrate the efficacy of the system as > 98.6% of infectious MNV-1 and > 96.3% PEDV were inactivated. Graphical Abstract: ga1 Highlights: Ozone inactivated SARS-CoV-2 surrogate and enteric virus in laboratory and public transport units. 2Log disinfection yield is attained for [O3 ] = 50 ppm (107 mg N m −3 ) within 20 min. The CFD code integrates an ozone self-decomposition and the ozone surface reaction models. The model predicts the ozone concentration distribution in all spaces/surfaces of the public transport units.